The Utilization of Cassava Leaf Meal (Manihot utilisima Pohl) in Feeds on Growth and Survival of Tambaqui (Colossoma macropomum) - Nugie Nugraha; Indra Suharman; Adelina Adelina (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Cassava leaf could potentially used as one of feed ingredient for fish, as it contained relatively high nutritional value and was easily obtained. However, these leaf contained quite high level of crude fiber. One of the efforts to descrease the crude fiber contain was by fermentation process. By using the process, fermented cassava leaf meal could increased the nutrient content, that was by drecusyng the value of crude. This research was conducted for 56 days at the fish nutrition laboratory and the Fisheries and Marine Reservoir, University of Riau. This research was aimed to observe the influence of fermented cassava leaf meal (Manihot utilissima Pohl) in the diet tambaqui (C. Macropomum) growth. This study used a completely randomized design (CRD) with 5 levels of treatment with 3 replications. The test feed used was artificial feed with a protein content of 30% and containing fermented cassava leaf meal (TFDS) of 0, 5, 10, 15 and 20%. The variables measure included the relative growth rate (RGR), efficiency of feed utilization (EPP), protein efficiency ratio (PER) and survival rate (SR). The results showed that fermented cassava leaf meal affected significant (P<0.05) on the RGR, EPP and PER, whereas survival rate was not significant (P>0.05). The results showed that the best treatment is P4 (TFDS 20%) with feed digestibility 58,33%, protein digestibility 85,31%, feed efficiency 41,19%, protein retention 28,62% and specific growth rate 3,54% and Survival rate is 96,66%. The results of water quality measurements during maintenance temperature ranged 27-30°C, pH 5.6-7.0, DO 6.3-7.0 mg/L.